Kenya Social Protection Sector Review : Executive Report - World Bank; Republic of Kenya Ministry of State for Planning (Nairobi, 2014)
There is now broad consensus among policymakers that social protection is a powerful way to fight poverty and promote inclusive growth. This international consensus is most clearly articulated in the African Union's Social Policy Framework (SPF), which was endorsed by all African heads of state in 2009. The SPF explains that social protection includes 'social security measures and furthering income security; and also the pursuit of an integrated policy approach that has a strong developmental focus, such as job creation' the SPF commits governments to progressively realizing a minimum package of essential social protection that covers essential health care and benefits for children, informal workers, the unemployed, the elderly, and people with disabilities. Kenya has a long history of investing in social protection. Social protection in Kenya is defined as 'policies and actions, including legislative measures, that enhance the capacity of and opportunities for the poor and vulnerable to improve and sustain their lives, livelihoods, and welfare, that enable income-earners and their dependents to maintain a reasonable level of income through decent work, and that ensure access to affordable healthcare, social security, and social assistance.' However, the coverage of its social insurance schemes and safety net programs has tended to be low and their effectiveness limited. In 2005/06 the rate of poverty was 47 percent, although poverty rates were markedly higher in rural areas (50 percent) than in urban areas (34 percent). They also varied among provinces from a high of 74 percent in the North Eastern province to a low of 22 percent in Nairobi. This persistent poverty highlights the fact that social protection can play an important role in the effort to reduce poverty and promote human development in Kenya.